Chemogenetic activation of oxytocin neurons: temporal dynamics, hormonal release, and behavioral consequences - Grund, Thomas; Tang, Yan; Benusiglio, Diego; Althammer, Ferdinand; Probst, Sophia; Oppenländer, Lena; Neumann, Inga D.; Grinevich, Valéry (Psychoneuroendocrinology, 2019)
Chemogenetics provides cell type-specific remote control of neuronal activity. Here, we describe the application of chemogenetics used to specifically activate oxytocin (OT) neurons as representatives of a unique class of neuroendocrine cells. We injected recombinant adeno-associated vectors, driving the stimulatory subunit hM3Dq of a modified human muscarinic receptor into the rat hypothalamus to achieve cell type-specific expression in OT neurons. As chemogenetic activation of OT neurons has not been reported, we provide systematic analysis of the temporal dynamics of OT neuronal responses in vivo by monitoring calcium fluctuations in OT neurons, and intracerebral as well as peripheral release of OT. We further provide evidence for the efficiency of chemogenetic manipulation at behavioral levels, demonstrating that evoked activation of OT neurons leads to social motivation and anxiolysis. Altogether, our results will be profitable for researchers working on the physiology of neuroendocrine systems, peptidergic modulation of behaviors and translational psychiatry.